Analisis Bibliometrik Penggunaan Media Pembelajaran Fisika Terhadap Kemampuan Berpikir Kritis Siswa Pada Tahun 2015-2022 - Esti Muzayyanah; Dwi Putri Natalia; Yoga Budi Bhakti (UNIVERSITAS INDRAPRASTA PGRI, 2022)
The ability to think critically is one of the skills that everyone should have in this 21st century that we are living. In physics subjects, this skill is urgently needed to understand concepts. However, educators in Indonesia are still limited to using learning media, so we researchers want to provide a broad picture of the use of innovative learning media on the critical thinking ability of students in physics learning. This research method uses literature studies with bibliometric analysis. . Research data was obtained from 236 articles selected through Publish or Perish which is indicated by Google Scholar from 2015-2022 in the form of article journals. The results of the data analysis show the development of trends in the use of physics learning media to students' critical thinking ability in the year has the highest graph in 2021 and the lowest in 2022. After filtering from 236 articles to the top 10 articles, the institution where the publication contributed a lot of research came from Sebelas Maret University with a total of 31 publications. The most contributor to the research is Sudarti who has published 5 articles. In the visualization display of the medium, it can be shown if the use of technology-based types of learning media can grow students' critical thinking skills. In addition, in the display of critical thinking ability visualization, the role of educators in influencing students in the learning process can improve students' critical thinking skills depending on the learning model used.